2021
DOI: 10.1038/s42003-021-02545-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis in yeast reveals a meiosis-specific actin-containing nuclear bundle

Abstract: Actin polymerises to form filaments/cables for motility, transport, and the structural framework in a cell. Recent studies show that actin polymers are present not only in the cytoplasm but also in the nuclei of vertebrate cells. Here, we show, by electron microscopic observation with rapid freezing and high-pressure freezing, a unique bundled structure containing actin in the nuclei of budding yeast cells undergoing meiosis. The nuclear bundle during meiosis consists of multiple filaments with a rectangular l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…A recent study also reported novel meiotic intranuclear filaments in yeast cells [ 44 ], though it is unclear if those filaments are triple-helical. Nevertheless, the similar abundance and bundling phenotypes suggest that the filaments observed by Takagi, et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study also reported novel meiotic intranuclear filaments in yeast cells [ 44 ], though it is unclear if those filaments are triple-helical. Nevertheless, the similar abundance and bundling phenotypes suggest that the filaments observed by Takagi, et al .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Takagi et al . provided immuno-EM evidence that the similar filaments they saw (probably MTHs) contain actin [ 44 ]. While MTHs cannot be F-actin, which would appear double helical, they could instead be a non-canonical triple-helical polymer of actin that is sensitive to Lat-A and is bound by anti-actin antibodies in immuno-EM experiments, but unable to bind rhodamine-phalloidin and Lifeact.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, that some studies also report polymerized filamentous actin in the nucleus of diverse organisms, however, its structural properties are still under-researched, and outside of the animal kingdom this issue has received little attention to date [73][74][75][76][77][78]. For reviews see [79][80][81].…”
Section: The Relation Between Actin and Chromatin Remodelling: Arp8 A...mentioning
confidence: 99%
“…It should be noted, that some studies also report polymerized filamentous actin in the nucleus of diverse organisms, however, its structural properties are still under‐researched, and outside of the animal kingdom this issue has received little attention to date (Andrin et al, 2012; Belin, Lee, & Mullins, 2015; Lestourgeon, Forer, Yang, Bertram, & Pusch, 1975; McDonald, Carrero, Andrin, de Vries, & Hendzel, 2006; Schoenenberger et al, 2005; Takagi, Osumi, & Shinohara, 2021). For reviews see (Castano et al, 2010; Gettemans et al, 2005; Pederson & Aebi, 2002).…”
Section: Actin‐related Ir‐sensitive Yeast Deletion Mutantsmentioning
confidence: 99%